Comparative proteomics reveals signature metabolisms of exponentially growing and stationary phase marine bacteria. (3rd April 2017) - Muthusamy, Saraladevi; Lundin, Daniel; Mamede Branca, Rui Miguel; Baltar, Federico; González, José M.; Lehtiö, Janne; Pinhassi, Jarone
Summary: Much of the phenotype of a microorganism consists of its repertoire of metabolisms and how and when its proteins are deployed under different growth conditions. Hence, analyses of protein expression could provide important understanding of how bacteria adapt to different environmental settings. To characterize the flexibility of proteomes of marine bacteria, we investigated protein profiles of three important marine bacterial lineages – Oceanospirillaceae ( Neptuniibacter caesariensis strain MED92), Roseobacter ( Phaeobacter sp. MED193) and Flavobacteria ( Dokdonia sp. MED134) – during transition from exponential to stationary phase. As much as 59–80% of each species' total proteome was expressed. Moreover, all three bacteria profoundly altered their expressed proteomes during growth phase transition, from a dominance of proteins involved in translation to more diverse proteomes, with a striking appearance of enzymes involved in different nutrient‐scavenging metabolisms. Whereas the three bacteria shared several overarching metabolic strategies, they differed in important details, including distinct expression patterns of membrane transporters and proteins in carbon and phosphorous metabolism and storage compounds. These differences can be seen as signature metabolisms – metabolisms specific for lineages. These findings suggest that quantitative proteomics can inform about the divergent ecological strategies of marine bacteria in adapting to changes in environmental conditions.